Bleeding in Critically Ill Children—Review of Literature, Knowledge Gaps, and Suggestions for Future Investigation - Aran, Adi Avniel; Karam, Oliver; Nellis, Marianne E. (Frontiers in Pediatrics, 2021)
Clinically significant bleeding complicates up to 20% of admissions to the intensive care unit in adults and is associated with severe physiologic derangements, requirement for significant interventions and worse outcome. There is a paucity of published data on bleeding in critically ill children. In this manuscript, we will provide an overview of the epidemiology and characteristics of bleeding in critically ill children, address the association between bleeding and clinical outcomes, describe the current definitions of bleeding and their respective limitations, and finally provide an overview of current knowledge gaps and suggested areas for future research.